GAMBARAN PENGETAHUAN CAREGIVER DALAM MENDETEKSI DINI RISIKO LUKA KAKI DIABETES DI PUSKESMAS ANTANG PERUMNAS KOTA MAKASSAR - Rasimin, Rosmini; Bubun, Juhelnita; Sintawati, Sintawati (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2024)
Background: The main causes of LKD are neuropathy and PAD. To prevent LKD, caregivers can perform the Ipswich touch test (IpTT) to detect neuropathy and check the dorsalis pedis (DP) and posterior tibialis (PT) pulses to detect PAD. IpTT and DP and PT pulse checks are simple examinations and can be performed by non-professionals. Objective: to determine the description of caregiver knowledge about IpTT and DP and PT pulse checks. Method: This study used a cross-sectional design. The sampling technique used was purposive sampling, the number of samples was 59. Results: caregivers have insufficient knowledge about IpTT and also still have insufficient knowledge about DP and PT pulse examinations. Conclusion: Caregivers have insufficient knowledge about IpTT to detect neuropathy and PT and DP examinations to detect PAD.